2018
DOI: 10.1016/j.foodchem.2017.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Structurally modified pectin for targeted lipid antioxidant capacity in linseed/sunflower oil-in-water emulsions

Abstract: The present work explored the lipid antioxidant capacity of citrus pectin addition to 5%(w/v) linseed/sunflower oil emulsions stabilized with 0.5%(w/v) Tween 80, as affected by pectin molecular characteristics. The peroxide formation in the emulsions, containing tailored pectin structures, was studied during two weeks of storage at 35°C. Low demethylesterified pectin (≤33%) exhibited a higher antioxidant capacity than high demethylesterified pectin (≥58%), probably due to its higher chelating capacity of pro-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…A further increase in pectin concentration from 0.05 to 0.1% (w/v) did not lead to a clear difference in the lipid antioxidant capacity of LM or HM pectin (Chen et al., ), whereas according to Celus et al. (), a further increase in citrus pectin concentration from 0.1 to 1 % (w/v) in the aqueous phase of linseed/sunflower o/w emulsions (5% w/v) stabilized by Tween 80 (0.5% w/v) was accompanied by a significant decrease in lipid oxidation. Despite the fact that emulsion destabilization was observed for the o/w emulsions containing 1% pectin (w/v), it can be suggested that increasing pectin concentration results in a decrease in lipid oxidation, given the higher number of negatively charged carboxyl groups present to bind Fe 2+ .…”
Section: Pectin Functionalities Based On Cation Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further increase in pectin concentration from 0.05 to 0.1% (w/v) did not lead to a clear difference in the lipid antioxidant capacity of LM or HM pectin (Chen et al., ), whereas according to Celus et al. (), a further increase in citrus pectin concentration from 0.1 to 1 % (w/v) in the aqueous phase of linseed/sunflower o/w emulsions (5% w/v) stabilized by Tween 80 (0.5% w/v) was accompanied by a significant decrease in lipid oxidation. Despite the fact that emulsion destabilization was observed for the o/w emulsions containing 1% pectin (w/v), it can be suggested that increasing pectin concentration results in a decrease in lipid oxidation, given the higher number of negatively charged carboxyl groups present to bind Fe 2+ .…”
Section: Pectin Functionalities Based On Cation Interactionsmentioning
confidence: 99%
“…Despite the fact that several pectin structural properties, such as DM, DB, DP, or DAc, have been suggested to direct its divalent cation‐chelating capacity and, thus, its lipid antioxidant capacity, only the effect of pectin DM and DB abs on the oxidative stability of o/w emulsions has been reported in the literature. The lipid antioxidant capacity of pectin is reported to be more pronounced at low DM, due to the higher number of negative charges, which is associated with a higher Fe 2+ ‐binding capacity (Celus et al., ; Chen et al., ). In contrast, pectin DB abs reportedly does not have a large influence on its lipid antioxidant capacity (Celus et al., ).…”
Section: Pectin Functionalities Based On Cation Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…But the oxidative stability could be restored when the proteins were added back, mainly due to iron‐binding capacity of the unabsorbed proteins. Addition of other types of biopolymers in O/W emulsions, which are not intended to be used as emulsifiers, have also been reported to exhibit antioxidant capacity such as casein (Chen et al., ), citrus pectin (Celus et al., ), and sodium alginate (Salvia‐Trujillo, Decker, & Mcclements, ), to name a few. In addition, a recent work by Johnson, Inchingolo, and Decker () has reported that oxygen content in a fish oil‐in‐water system could be reduced by ≥95% by using commercially accessible oxygen scavenging packaging, which significantly improved the emulsion oxidative stability.…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 99%